(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background & objectives- Nursing profession is very stressful profession by its demands and nature of work. The main objective of this study is to compare the stress levels among nurses depending on their years of experience. Method- A non probability convenience sampling technique was adopted to select 300 registered nurses from different working area of Krishna Hospital & Medical Research Centre, Karad.Modified expanded nursing stress scale (MENSS) was used to collect data. Result- 64.3% (193) nurses were having 1 to 5 years work experience and 23.7% (71) had 6 to 10 years where as very few 2.7% (8), 3.7% (11)and 5.7% (17) nurse are from respectively 11 to 15, 16 to 20 and more than 20 years of experience. Nurses with more than 5years of experience. Nurses with lower experience having higher moderate stress where as higher experience having higher severe stress. There was statistically significant association between the levels of stress with Years of experience having a computed chi- square ( 2) value19.830 with p value 0.011 were associated with the levels of stress. Conclusion -Though there has been adequate clinical skills training in the nursing curriculum, little attention is paid to make the working environment less stressful and more conducive to healthy interactions. Emotional preparation of nurses in dealing with patients is required. Need to use Stress reduction activities and measures to handle stressful situation and interpersonal stress.